Hospitalization of Children Aged <5 Years Due to Influenza: Study Based on the National Hospitalization Registry - Krzysztof Kanecki; Katarzyna Lewtak; Paweł Goryński; Piotr Tyszko; Magdalena Bogdan; Michał Rząd; Aneta Nitsch-Osuch (MDPI AG, 2022)
Background: Influenza constitutes a significant health care burden that can be related to an increased morbidity and mortality. The aim of the study is to show up-to-date information on influenza hospitalization cases in Poland in children aged <5 years. Methods: The data used in the study were hospitalization records from 2015-2019, which had been gathered in a Nationwide General Hospital Morbidity Study and made available by the National Institute of Public Health. Results: 8565 records of patients with influenza were subject to analysis. The mean and median age of the patients were 2.2 and 2.1 years, respectively. Influenza hospitalization incidence was estimated at 90 per 100,000 person-years (PY) in children aged <5 years. The number of hospitalization cases was significantly higher in patients living in urban regions than in those living in rural regions (97 vs. 77 per 100,000 PY; p < 0.001). The age of patients living in urban regions was significantly lower than the age of patients living in rural regions (2.2 vs. 2.3 years; p < 0.001). A statistically significant increase in hospitalization was observed. Conclusions: The reported increasing trend in hospitalizations indicates the need to take focused measures. Presented data may be useful in comparative analyses in a European context.